Between the Motives of Carrying Out Religious Orders and Political Interests - Suaib, Muh Ridha; Hatta, Muhammad; Purnomo, Ari; Arief, Anggreany; Moonti, Roy Marthen (International Journal of Psychosocial Rehabilitation, 2020)
The motives for the occurrence of criminal acts of terrorism do not stand alone but are multi- motivated, such as injustice, poverty, ignorance and the ease of getting information from virtual media so that certain individuals or groups are affected by the ideas of radicalism and terrorism which are widely spread in various media. In addition, there are several terrorist groups that carry out their actions on the basis of carrying out certain religious orders. Terrorists generally refer to themselves as separatists, liberation fighters, crusaders, militants, mujahideen, and other terms in accordance with their religion. However, the cause of terrorism thrives in Indonesia is not only ignorance, poverty, perversion of religious understanding but the existence of political interests and different political views. In Article 1 paragraph 2 of Law No. 5 of 2018 concerning Eradication of Terrorism Criminal Acts is formulated that acts of terrorism are not only based on certain religious ideologies, disturbance to the stability of national security but acts of terrorism are based on political interests.